LEMBAGA PERWATIN DAN KEPUNYIMBANGAN DALAM MASYARAKAT ADAT LAMPUNG: ANALISIS ANTROPOLOGIS - Irham, Muhammad Aqil (Analisis: Jurnal Studi Keislaman, 2013)
The  indigenous  society  of Lampung  is divided  into  two  large groups; Saibatin and Pepadun. Both societies has many diversities in origins, so the local government arrangements is stimulated  in the consultative  mechanism represented  by punyimbang at each level within the representative  agency called Perwatin ( Proatin ). With anthropologic analysis , this paper would like to emphasize the meaning , role and function  of institutional of Perwatin  and Kepunyimbangan   for  indigenous   peoples  of  West   Lampung, its relevance to contemporary of democratic values, and the opportunities   and  the  existence  of  the  traditional   institutions in  the  implementation  of  the  reform  of  Regional  Autonomy Law . According  to the findings of the research,   prowatin  and punyimbangan   are  still   very   important   to   be  implemented in local communities in West Lampung. This is case due to democratic   values  and  local  wisdom  in  prowatin  institutions and kepenyimbangan accordance with the conditions of the community and institutional environment in which it arise.